MOTIVATING THE FIRST YEAR STUDENTS OF SMP WAHYU MAKASSAR TO MASTER ENGLISH VOCABULARY USING QUESTIONS - Robertina Ule Ngey. (Publikasi dan UKI Press UKI Toraja., 2022)
The purpose of this writing is to know the effect of using Questions in motivating students to master English vocabulary of SMP Wahyu Makassar. This research is experiment research that according to students ‘vocabulary knowledge. The population in this research is students’ class VII-A of SMP Wahyu Makassar with number of sample 25 students. This research holds on January 2016. In this research, the writer used test as the instrument that given on pre-test and post-test. The result of research showed that with using questions method in teaching and learning English process can improving students’ vocabulary of SMP Wahyu Makassar. In other words, with using questions can giving positive effect to students. Using questions in this research can be said success because can improving students’ vocabulary.